A Dansyl Amide N‐Oxide Fluorogenic Probe Based on a Bioorthogonal Decaging Reaction. Issue 10 (12th October 2021) - Yang, Hong; Wang, Yongcheng; Li, Xiang; Teng, Yu; Tian, Yulin
Abstract: A smart fluorescence "turn‐on" probe which contained a dansyl amide fluorophore and an N ‐oxide group was designed based on the bioorthogonal decaging reaction between N ‐oxide and the boron reagent. The reaction proceeds in a rapid kinetics ( k 2 =57.1±2.5 m −1  s −1 ), and the resulting reduction product showcases prominent fluorescence enhancement (up to 72‐fold). Time dependent density functional theoretical (TD‐DFT) calculation revealed that the process of photoinduced electron transfer (PET) from the N ‐oxide moiety to the dansyl amide fluorophore accounts for the quenching mechanism of N ‐oxide. This probe also showed high selectivity over various nucleophilic amino acids and good biocompatibility in physiological conditions. The successful application of the probe in HaloTag protein labeling and HepG2 live‐cell imaging proves it a valuable tool for visualization of biomolecules. Abstract : A smart fluorescence "turn‐on" probe, DASNox, which contained a dansyl amide fluorophore and an N ‐oxide group, was designed based on the bioorthogonal decaging reaction between N ‐oxide and the boron reagent. DASNox showed good biocompatibility in physiological conditions and has been successfully applied in HaloTag protein labeling and HepG2 live‐cell imaging. This bioorthogonal decaging reaction has enriched the chemical biology toolkit and offered an effective way for visualization and detection of biomolecules in vivo.